2009
DOI: 10.4103/0972-0707.53340
|View full text |Cite
|
Sign up to set email alerts
|

Permanent molar pulpotomy with a new endodontic cement: A case series

Abstract: The aim of this case series was to determine the clinical and radiographic success rate of pulpotomy, with new endodontic cement (NEC), in human mature permanent molar teeth. Twelve molars with established irreversible pulpitis were selected from patients 14 – 62 years old. The selection criteria included carious pulp exposure with a positive history of lingering pain. After isolation, caries removal, and pulp exposure, pulpotomy with NEC was performed and a permanent restoration was immediately placed. At the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 27 publications
(52 reference statements)
3
68
0
2
Order By: Relevance
“…Biochemical assays that evaluate the effects of dental materials on genetic tissues are relevant for minimizing risks to patients and clinicians. Antibacterial activity, cytotoxicity, clinical applications, and subcutaneous tissue reactions of CEM have been evaluated in several studies [24][25][26][27][28][29][30] . To our knowledge, however, this is the first study in which the genotoxic effects of CEM have been demonstrated in vitro by a single-cell gel electrophoresis (comet) assay.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical assays that evaluate the effects of dental materials on genetic tissues are relevant for minimizing risks to patients and clinicians. Antibacterial activity, cytotoxicity, clinical applications, and subcutaneous tissue reactions of CEM have been evaluated in several studies [24][25][26][27][28][29][30] . To our knowledge, however, this is the first study in which the genotoxic effects of CEM have been demonstrated in vitro by a single-cell gel electrophoresis (comet) assay.…”
Section: Discussionmentioning
confidence: 99%
“…3,14,16,25,26 However, the treatment technique in these studies is full pulpotomy, which often causes negative response to pulp vitality tests in follow-up sessions. By saving coronal pulp in the DPC technique, the clinician has the opportunity to perform pulp vitality tests in addition to periapical and radiographic examinations and to compare them with the baseline data and draw a distinct conclusion about pulp status.…”
Section: Discussionmentioning
confidence: 99%
“…Biological responses (the quality of dentinal bridges and the amount of pulp inflammation) after DPC with CEM cement and MTA were similar and better than CH in dogs' teeth. 13 CEM cement has been used successfully in pulpotomy of inflamed mature 14 and immature 15,16 human teeth. Two recent histological studies on DPC of healthy human teeth demonstrate similar biological responses to CEM cement and MTA.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered as the foundation of experimental research. It can contribute to medical science in two ways; as a source of new knowledge and in medical education and audit 6,8,47,56,[60][61][62][63][64] . Useful information and evidences also can be synthesized by doing meta-analysis of case reports 7 .…”
Section: Case Report As a Foundation Of Researchmentioning
confidence: 99%